Farmers, agriculture and the UNFCCC - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
In conjunction with the UNFCCC COP20 in Lima, Peru, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) hosted a half-day event to raise awareness among farmers’ representatives and youth representatives on the status of agriculture in the negotiations, provide a networking space for farmers, and also exchange ideas on influencing agriculture in the UNFCCC going forward to the post-2015 agreement and beyond.